Extracellular Matrix Remodeling of the Umbilical Cord in Pre-eclampsia as a Risk Factor for Fetal Hypertension - Lech Romanowicz; Zofia Galewska (Journal of Pregnancy)
The human umbilical cord forms a connection between the placenta and the foetus. It is composed of two arteries and one vein surrounded by Wharton's jelly. Pre-eclampsia is accompanied by extensive remodeling of extracellular matrix of umbilical cord. Matrix metalloproteinases (MMPs) are engaged in degradation of extracellular matrix proteins and activation/inactivation of certain cytokines and enzymes. These enzymes will probably play a central role in the release of matrix-embedded cytokines and growth factors. MMP-2 (gelatinase A) is the main collagenolytic enzyme of both umbilical artery and vein. Other metalloproteinases are present in several times lower amounts. Reduced activity of collagen-degrading enzymes may be a factor, which enhances the accumulation of collagen and some other proteins in the pre-eclamptic umbilical cord tissues. It seems to be possible that similar alterations occur in other fetal blood vessels. It may result in an increase in peripheral resistance as well as an increase in the blood pressure in the fetal vascular system. Some observations suggest that the raised pressure may persist after birth. Pre-eclampsia may be a factor that evokes an initiation of hypertension in utero and its amplification through childhood and adulthood.